Reading the Irish Woman : Studies in Cultural Encounters and Exchange, 1714-1960 - Meaney, Gerardine, 1962-; Whelan, Bernadette; O'Dowd, Mary (Book collections on Project MUSE., 2013)
The first analysis of the Enlightenment and Irish women and the most comprehensive study to date of Irish women and American emigration. Irish women negotiated, selected and at times defied the representations of womanhood presented to them in official and commercially sponsored media.